ETIKA DAN KEPATUHAN PAJAK - Amalia Hasanah; Lilis Ardini (Faculty of Economic and Business Universitas STIKUBANK, 2021)
National income is from tax revenue. Every year the tax revenue target always increases, but since 2008, the target revenue has never been able to. In addition, the tax compliance of the taxpayers in the DJP performance report shows a low percentage, even though taxpayers are expected to increase state revenue. There are many taxpayers who tax taxes illegally. So the question arises about how taxpayers' ethics taxation. This article is a conceptual article that is conducted based on the author's ideas and opinions . Keywords : ethics, taxation, tax compliance